Improving the Method of Forming the Geo-Information Base of Population Point Land (Texas Journal of Engineering and Technology, 2022)
This scientific article focuses on the issues of forming the calculation of residential areas in the geodatabase and determining periodic changes. A scientific result dedicated to the automation of the system of determining the dynamics of their change based on the algorithm of the remote study of the residential areas of the population with the help of software belonging to the family of the geoinformation system is counted.